(untitled) (World Economics and Finance Bulletin, 2024)
This article explores the nutritional status of military personnel across various operational environments, including combat zones, training exercises, and garrison settings. It examines the implications of nutrition on military performance, health, and readiness, drawing from a review of current literature and empirical data.